2011
DOI: 10.1016/j.jbmt.2010.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between measures of dysfunctional breathing in a population with concerns about their breathing

Abstract: DB cannot be simply defined. For practical purposes DB is probably best characterised as a multi-dimensional construct with at least 3 dimensions, biochemical, biomechanical and breathing related symptoms. Comprehensive evaluation of breathing dysfunction should include measures of breathing symptoms, breathing pattern, resting CO(2) and also include functional measures such a breath holding time and response of breathing to physical and psychological challenges including stress testing with CO(2) monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 44 publications
3
63
0
Order By: Relevance
“…Data from this study are similar to those of Courtney et al 21 who demonstrated that DB has three distinct dimensions and that they often do not correlate well, suggesting a need to screen for the condition of DB overall and then have further assessments that can be performed to identify which dimension(s) of DB, if any, are present. These data are in agreement with Bradley 11 as well where they showed a relationship between two of the three dimensions of DB but that all three were not closely correlated, again suggesting the need to assess for all three dimensions.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Data from this study are similar to those of Courtney et al 21 who demonstrated that DB has three distinct dimensions and that they often do not correlate well, suggesting a need to screen for the condition of DB overall and then have further assessments that can be performed to identify which dimension(s) of DB, if any, are present. These data are in agreement with Bradley 11 as well where they showed a relationship between two of the three dimensions of DB but that all three were not closely correlated, again suggesting the need to assess for all three dimensions.…”
Section: Discussionsupporting
confidence: 76%
“…11 Recently, researchers have identified the three most common dimensions or categories of DB which include the biochemical, biomechanical and psychophysiological dimensions. 21 It has been suggested that any comprehensive assessment for DB should include tools that capture all three of these dimensions as they are often found to be independent from each other.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that, other than MARM and the Nijmegen questionnaire (which correlate weakly), these methods have yet to been shown to correlate with one another [31].…”
Section: Methods Of Assessmentmentioning
confidence: 99%
“…Some now suggest that a broader characterisation is required as DB related signs and symptoms, especially those associated with a perception of breathing restriction, cannot always be attributed to hyperventilation (Courtney and van Dixhoorn 2014). These symptoms have very weak correlations with carbon dioxide levels (Courtney et al 2011a) and cannot be reproduced with voluntary hyperventilation and hypocapnia (Hornsveld et al 1996).…”
Section: Introductionmentioning
confidence: 99%